2023
DOI: 10.18632/aging.205202
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box-1 impedes skeletal muscle regeneration via downregulation of Pax-7 synthesis by increasing miR-342-5p expression

Trung-Loc Ho,
Yu-Liang Lai,
Chin-Jung Hsu
et al.

Abstract: High mobility group box-1 (HMGB1) is a driver of inflammation in various muscular diseases. In a previous study, we determined that HMGB1 induced the atrophy of skeletal muscle by impairing myogenesis. Skeletal muscle regeneration after injury is dependent on pair box 7 (Pax-7)-mediated myogenic differentiation. In the current study, we determined that the HMGB1-induced downregulation of Pax-7 expression in myoblasts inhibited the regeneration of skeletal muscle. We also determined that HMGB1 inhibits Pax-7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…Unfortunately, we could not clarify the mechanisms and/or the triggers of the expressional changes in miRs by intravitreal NMDA in the present study. Recently, the high-mobility group box-1 (HMGB1)-receptor of advanced glycation end-products (RAGE) axis has been found to be involved in the regulation of miR expression [26,27]. We previously reported that the HMGB1-RAGE axis was involved in neurodegeneration induced by intravitreal NMDA in the retina [28].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we could not clarify the mechanisms and/or the triggers of the expressional changes in miRs by intravitreal NMDA in the present study. Recently, the high-mobility group box-1 (HMGB1)-receptor of advanced glycation end-products (RAGE) axis has been found to be involved in the regulation of miR expression [26,27]. We previously reported that the HMGB1-RAGE axis was involved in neurodegeneration induced by intravitreal NMDA in the retina [28].…”
Section: Discussionmentioning
confidence: 99%